Bidirectional leader development in a preexisting channel as observed in rocket‐triggered lightning flashes. Issue 2 (17th January 2017) - Qie, Xiushu; Pu, Yunjiao; Jiang, Rubin; Sun, Zhuling; Liu, Mingyuan; Zhang, Hongbo; Li, Xun; Lu, Gaopeng; Tian, Ye
Abstract: Two cases of bidirectional leader, starting almost immediately below a decaying dart or dart‐stepped leader which terminated before reaching the ground, were identified, for the first time, in rocket‐triggered lightning flashes based on high‐speed video, electric field changes, and channel base current, indicating that a bidirectional leader can be excited by a decayed dart leader and propagate in a preexisting discharge channel. The positive end of the bidirectional leader moved upward along the terminated downward dart leader path, and the negative end extended downward along the decayed initial continuous current or preceding stroke path to the ground and culminated in a return stroke. The positive leader propagated with an average speed of 1.3 × 10 6  m/s and 2.2 × 10 6  m/s in the two cases, roughly twice as fast as its negative counterpart with speed of 7.8 × 10 5  m/s and 1.0 × 10 6  m/s, respectively. The positive end started earlier than the negative end with a preceding time less than 40.3 µs. The bidirectional leader can be regarded as a recoil leader with the positive end retrogressing along a negative leader channel, whose polarity is contrary to the traditional recoil leader with negative leader end retrogressing along an existing positive leader channel. Weak luminosity was continuously observed during the terminated dart leader and bidirectional leader stage, but the channel current was less than the minimum detection capability of 9.3 A. Key Points: Bidirectional leader in a preexisting discharge channel was documented in rocket‐triggered lightning flashes The positive end moving upward along the decayed dart leader path started earlier and propagated twice as fast as the negative end The bidirectional leader can be regarded as a recoil leader but with polarity being contrary to the traditional recoil leader